Magnetization Analysis of Oriented Chains of Hexagonal Cobalt Nanoplates - Casagrande-Denardin, J (American Institute of Physics, 2014)
High quality single-crystalline hexagonal cobalt nanoplates have been obtained by a simple chemical reduction method using ultrasonic assistance. Individual nanoplates tend to form agglomerates due to their strong in-plane anisotropy. These particles were incorporated within a polyethylene matrix by a solution blending method and arrays of magnetic chains were generated by solidification of the solution of nanoparticles in the presence of a magnetic field. The easy axis of the Co plates is oriented along the field, in the direction of the chains length. Micromagnetic simulations, magnetic measurements, and FORC diagrams are used to clarify the complex magnetic behavior in these systems. (C) 2014 AIP Publishing LLC.